The prognostic value of BRAF mutation in colorectal cancer and melanoma: a systematic review and meta-analysis. - Gholamreza Safaee Ardekani; Seyed Mehdi Jafarnejad; Larry Tan; Ardavan Saeedi; Gang Li (PLoS ONE)
Background Mutation of BRAF is a predominant event in cancers with poor prognosis such as melanoma and colorectal cancer. BRAF mutation leads to a constitutive activation of mitogen activated protein kinase pathway which is essential for cell proliferation and tumor progression. Despite tremendous efforts made to target BRAF for cancer treatment, the correlation between BRAF mutation and patient survival is still a matter of controversy. Methods/principal findings Clinical studies on the correlation between BRAF mutation and patient survival were retrieved from MEDLINE and EMBASE databases between June 2002 and December 2011. One hundred twenty relevant full text studies were categorized based on study design and cancer type. Publication bias was evaluated for each category and pooled hazard ratio (HR) with 95% confidence interval (CI) was calculated using random or fixed effect meta-analysis based on the percentage of heterogeneity. Twenty six studies on colorectal cancer (11,773 patients) and four studies on melanoma (674 patients) were included in our final meta-analysis. The average prevalence of BRAF mutation was 9.6% in colorectal cancer, and 47.8% in melanoma reports. We found that BRAF mutation increases the risk of mortality in colorectal cancer patients for more than two times; HR = 2.25 (95% CI, 1.82-2.83). In addition, we revealed that BRAF mutation also increases the risk of mortality in melanoma patients by 1.7 times (95% CI, 1.37-2.12). Conclusions We revealed that BRAF mutation is an absolute risk factor for patient survival in colorectal cancer and melanoma.